Carbon footprint and urban planning : incorporating methodologies to assess the influence of the urban master plan on the carbon footprint of the city /: incorporating methodologies to assess the influence of the urban master plan on the carbon footprint of the city. (2016) - Zubelzu, Sergio; Fernández, Roberto Álvarez
No abstract available